Assessing polymyalgia rheumatica activity when C-reactive protein is unavailable or uninterpretable. (15th January 2018) - Devauchelle-Pensec, Valérie; Saraux, Lea; Berthelot, Jean Marie; De Bandt, Michel; Cornec, Divi; Guellec, Dewi; Marhadour, Thierry; Jousse-Joulin, Sandrine; Gouillou, Maelenn; Saraux, Alain
Abstract: Objective: The PMR activity score (PMR-AS) includes the CRP value, which may be lacking or invalid owing to anti-IL-6 therapy. Our objective was to develop alternatives to PMR-AS that do not require CRP. Methods: We used the Club Rhumatisme et Inflammation (CRI; 89 patients with PMR) and the Tolerance and Efficacy of tocilizumab iN pOlymyalgia Rheumatica (TENOR; 20 patients with recent-onset PMR naive to glucocorticoid who received three tocilizumab infusions, at weeks 0, 4 and 8, followed by prednisone from weeks 12 to 24) cohorts. In the CRI cohort, we evaluated correlations between PMR-AS items to select the best item for imputing CRP. Then we calculated the PMR-AS with (PMR-AS) and without (clin-PMR-AS) CRP and we used the linear regression between PMR-AS and clin-PMR-AS to obtain CRP-imputed (CRP-imp) PMR-AS. Finally, we evaluated agreement between clin-PMR-AS, CRP-imp PMR-AS, PMR-AS and ESR-PMR-AS in the TENOR cohort during tocilizumab therapy. Results: In the CRI cohort, agreement between PMR-AS and clin-PMR-AS was excellent (κ = 0.90). Linear regression between PMR-AS and clin-PMR-AS [CRP-imp PMR-AS = 1.12(clin-PMR-AS)+0.26] allowed us to build the CRP-imp PMR-AS. Mean (s.d. ) values were as follows: 8.40 (9.76) for PMR-AS, 7.24 (8.58) for clin-PMR-AS and 7.84 (9.61) for CRP-imp PMR-AS. CRP-imp PMR-AS agreed more closely with PMR-AS than did clin-PMR-AS. The results in the TENOR cohort confirmed that CRP-imp PMR-AS or ESR-PMR-AS could be used. Conclusion: Alternatives to the PMR-AS obtained without CRP can be used to monitor PMR activity in everyday practice in patients without available CRP values and in those receiving IL-6 antagonist therapy.